Aflatoksin: Cemaran dan Metode Analisisnya dalam Makanan - Aini, Nurul (Jurnal Kefarmasian Indonesia, 2012)
Aflatoxins are a group of natural contaminant produced by Aspergillus fungi. These mycotoxins are abundant in the area with high temperature and humidity, and have been classified as a carcinogenic agent to humans by IARC. Aflatoxin contamination could be found in food such as corn, nuts, rice, and milk. This review article suggests and discusses several methods that can be used to analyze aflatoxins in food and feed. These methods include ELISA, HPLC, and TLC Densitometry. This article was made with prior search of references from the internet and scientific journals. This review is aimed to compare the ability of these methods to analyze aflatoxin in food